1998
DOI: 10.1073/pnas.95.12.6947
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for organ allografts without using immunosuppressants or irradiation

Abstract: A strategy to achieve regular and long lasting organ and tissue allografts without using immunosuppressants and͞or irradiation has been established for mice. One hundred percent of skin allografts can be induced to survive >350 days after transplantation if spleen cells from the same donors are first injected into the portal vein of the recipients. The mechanisms underlying this long-term tolerance induction can be described as follows: (i) donor T cells from the spleen of the donor facilitate the acceptance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 32 publications
(24 reference statements)
2
49
0
Order By: Relevance
“…20 In this experiment, we have also shown that the existence of donor hematopoietic cells is crucial for the survival of donor PIs. In addition, we have recently shown the same findings in the transplantation of combinations of BMCs and other organs or tissue (such as the skin, leg and lung 18,[37][38][39] as in PI transplantation. Pham et al 40 and Foster et al 41 have also shown the importance of the existence of donor hematopoietic cells for the acceptance of the lung and composite tissue in the transplantation of the combination of BMCs and organs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…20 In this experiment, we have also shown that the existence of donor hematopoietic cells is crucial for the survival of donor PIs. In addition, we have recently shown the same findings in the transplantation of combinations of BMCs and other organs or tissue (such as the skin, leg and lung 18,[37][38][39] as in PI transplantation. Pham et al 40 and Foster et al 41 have also shown the importance of the existence of donor hematopoietic cells for the acceptance of the lung and composite tissue in the transplantation of the combination of BMCs and organs.…”
Section: Discussionsupporting
confidence: 49%
“…[14][15][16] We have developed more effective bone marrow transplantation (BMT) methods for the induction of acceptance of donor bone marrow cells (BMCs) than conventional intravenous injection of BMCs (IV-BMT); one method is BMC-transplantation into the liver via the PV (PV-BMT) and the other is intra-bone marrow (IBM)-BMT. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on our findings, we have developed a strategy to permit the long-term acceptance of allogeneic PIs by intra-hepatic transplantation of PIs plus whole-donor BMCs, followed by IV injection of whole BMCs on day 5 after PItransplantation without immunosuppressants in rats. 20 Although irradiation doses as pre-conditioning can be reduced in comparison with IV-administration of BMCs (IV-BMT), additional IV injection of BMCs is necessary in this method.…”
Section: Introductionmentioning
confidence: 99%
“…These anatomical features suggest that the liver may serve as a lymphoid organ wherein lymphocytes are activated by Ags circulating in the portal and arterial blood flow. In fact, administration of donor cells via the portal vein primes the recipient by the donor-Ags and leads to donor-Ag specific hyporesponsiveness (5)(6)(7)(8). Furthermore, the liver itself is such a tolerogenic organ that transplantation of an allogeneic liver sometimes requires little or no immunosuppressive therapy.…”
mentioning
confidence: 99%
“…Recently, we have found that the engraftment of allogeneic BMCs was significantly enhanced by administering BMCs via the portal vein [12]. Furthermore, we have succeeded in inducing persistent donor-specific tolerance across major histocompatibility complex (MHC) barriers utilizing the intrahepatic tolerance-inducing system in mice [13] and pigs [14]; the injection of donor BMCs via the p.v. (on day 0) plus i.v.…”
Section: Introductionmentioning
confidence: 99%
“…The skin grafting was carried out as previously described [13] on the day (but not on day 7) after the injection of donor BMCs (Fig. 1).…”
Section: Skin Graftingmentioning
confidence: 99%